Skeletal maturation in intrauterine growth-retarded rats treated with growth hormone - Quintero, Fabian Anibal (2004)
The objective of this study was to analyse the effects of intrauterine growth retardation (IUGR) and growth hormone (Gh) therapy on skeletal maturation in growth retarded rats. One-hundred and thirty-five rats constituted the groups: Control (C), Sham-operated (SH), IUGR and IUGR+Gh: injected with Genotropin 3.0 mg/kg/day) from 21 to 60 days of age. SH was injected only with saline solution. The thickness of tibial cartilage was assessed on X-ray at the ages 1, 21, 42, 63 and 84 days and categorised according to three levels. L1: maximal thickness, L2: reduction of 50% and L3: absence. The percentual differences between frequencies for each level were compared and clustered by simple ligation in Euclidean distance. The results lead to us to conclude that skeletal maturation does not appear to be modified by IUGR, while it is accelerated by growth hormone in growth-retarded rats.